Structural Features of Surface Layers of Bifunctional Polysiloxane Xerogels Containing 3-Aminopropyl Groups and 3-Mercaptopropyl Groups - Yuriy L. Zub; Inna V. Melnyk; Mark G. White; Bruno Alonso (Adsorption Science & Technology)
Polysiloxane xerogels containing both –SH and –NH 2 functions have been prepared using the sol–gel method with alkoxysilane precursors [such as Si(OEt) 4 , (MeO) 3 Si(CH 2 ) 3 SH and (EtO) 3 Si(CH 2 ) 3 NH 2 ]. Molar ratios of 3.2:1, 1.1:1 and 0.4:1 for the two functions –SH and –NH 2 were employed. Xerogels which contain only one of the two functions were also synthesized for comparative purposes. It was shown that the use of stannic compounds as catalysts for xerogels with 3-mercaptopropyl groups resulted in a product which possessed a non-porous structure, while the use of fluoride ions allowed the synthesis of a sample with a porous structure (S sp = 216 m 2 /g, V s = 0.152 cm 3 /g, d = 3.5 nm). Xerogels with a bifunctional surface layer possess a bimodal structure. Infrared, Raman and multinuclear solid-state NMR ( 1 H, 13 C, 29 Si) spectroscopy data showed: (i) the absence of deprotonation for the 3-mercaptopropyl groups in the bifunctional surface layer of the xerogels; and (ii) that 3-aminopropyl groups form hydrogen bonds in these surface layers. The type of hydrogen bond formed depends on the ratio of the amount of water to the amount of 3-aminopropyl groups in the surface layer. When this ratio is about 1:1, the amino group forms a hydrogen bond with the silanol group associated with the water molecule. Re-organization of the surface layer is observed when the amount of water decreases, the amino groups forming hydrogen bonds between themselves. Hence, the system of hydrogen bonds in the surface layer of such xerogels depends primarily on the drying regime employed for the samples.